Composition of Nonextractable Polyphenols from Sweet Cherry Pomace Determined by DART-Orbitrap-HRMS and Their In Vitro and In Vivo Potential Antioxidant, Antiaging, and Neuroprotective Activities - Domínguez-Rodríguez, Gloria; Ramón Vidal, Daniel; Martorell, Patricia; Plaza, Merichel; Marina, María Luisa (Journal of agricultural and food chemistry, 2022)
Sweet cherry pomace is an important source of phenolic compounds with beneficial health properties. As after the extraction of phenolic compounds, a phenolic fraction called nonextractable polyphenols (NEPs) remains usually retained in the extraction residue, alkaline and acid hydrolyses and enzymatic-assisted extraction (EAE) were carried out in this work to recover NEPs from the residue of conventional extraction from sweet cherry pomace. In vitro and in vivo evaluation of the antioxidant, antihypertensive, antiaging, and neuroprotective capacities employing Caenorhabditis elegans was achieved for the first time. Extractable phenolic compounds and NEPs were separated and identified by families by high-performance thin-layer chromatography (HPTLC) with UV/Vis detection. A total of 39 phenolic compounds were tentatively identified in all extracts by direct analysis in real-time high-resolution mass spectrometry (DART-Orbitrap-HRMS). EAE extracts presented the highest in vitro and in vivo antioxidant capacity as well as the highest in vivo antiaging and neuroprotective capacities. These results showed that NEPs with interesting biological properties are retained in the extraction residue, being usually underestimated and discarded.
Keywords: polyfenoly; Chromatography, High Pressure Liquid; nonextractable polyphenols; Prunus avium; Caenorhabditis elegans; antioxidancia; cherry pomace; direct analysis in real-time high-resolution mass spectrometry; Phenols; Plant Extracts; lidé; Antioxidants; high-performance thin-layer chromatography; fenoly; Humans; rostlinné extrakty; Polyphenols; vysokoúčinná kapalinová chromatografie